А Study on Derived Verbs Expressing Positive Emotions in the Mongolian Language (Mongolian Journal of Humanities and Social Sciences, 2025)
This study investigates the morphological structures of 117 Mongolian verbs denoting emotional states—specifically those expressing “Happiness,” “Perseverance,” and “Calmness.” —as documented in The Great Dictionary of the Mongolian Language (2016). The research aims to classify and analyze the derivational patterns of these emotion-related verbs based on their morphological formation and suffixal affixation, grounded in linguistic theory. The research is structured into three primary sections: 1. Derivational patterns of verbs associated with Happiness emotions; 2. Derivational patterns of verbs related to the expression of patience; 3. Derivational patterns of verbs expressing a calm emotional state. The study emphasizes that the lexical inventory of any language is intricately linked to the cultural, psychological, and social characteristics of its speakers. In this context, emotion-expressing verbs in Mongolian are analyzed through a linguistic lens, with a focus on their grammatical categories, derivational mechanisms, and semantic domains. Among the 117 verbs surveyed, 88 were found to be formed through suffixation. A total of nine suffixes were identified—namely -d, -j, -l, -r, -rkh, -s, -t, -ts, and -shaa—with -l and -r being the most frequently occurring. These suffixes demonstrate productive morphological processes in the formation of emotion-related verbs. The findings of this study are significant for deepening the understanding of Mongolian verb morphology and hold practical implications for language instruction, particularly in elucidating the etymology, structure, and semantic function of derived verbs to language learners.Монгол хэлний эерэг сэтгэл хөдлөл илэрхийлсэн үүсмэл үйл үгийн судалгааХураангуй: Тус өгүүлэлд “Монгол хэлний их тайлбар толь” (2016) бичгээс бүртгэж авсан нийт 117 үгийг  “Баярлах, Тэсвэр тэвчээртэй байх, Тайван байх” сэтгэл хөдлөлтэй холбоотой үйл үгийн бүтэх арга хэмээн утгын зүйлчлэлээр нь ангилсан бөгөөд тухайн үүсмэл үйл үгс ямар ямар дагаврын аргаар, хэрхэн бүтсэн зүй тогтлыг онолын суурь судалгаанд тулгуурлан тодорхойлов. Ингэхдээ үр дүнгийн хэсэгт судалгааны үндсэн агуулгыг 1. Баярлах сэтгэл хөдлөлтэй холбоотой монгол хэлний үйл үг бүтэх арга; 2. Тэсвэр тэвчээртэй байх сэтгэл хөдлөлтэй холбоотой монгол хэлний үйл үг бүтэх арга; 3. Тайван байх сэтгэл хөдлөлтэй холбоотой монгол хэлний үйл үг бүтэх арга хэмээн 3 хэсэгт авч үзэв.Аль ч хэлний үгийн санд сэтгэл хөдлөл илэрхийлсэн үг хэллэг байх ба тухайн үндэстний соёл, амьдралын хэв маяг, ёс заншил, сэтгэлгээний онцлогоос хамаараад тоо хэмжээний хувьд харилцан адилгүй байдаг. Бидний судалгааны ажил нь монгол хэлний эерэг сэтгэл хөдлөл илэрхийлсэн үйл үгийн хүрээнд хамрах ба эдгээр үг хэллэгийг холбогдох эх хэрэглэгдэхүүнээс бүртгэн авч, үгсийн аймаг, үг зүйн талаас нь судалж, тухайн үйл үгсийн бүтэх аргын талаар тодруулахыг зорив. Түүвэрлэн авсан 117 үгнээс 88 нь дагаврын аргаар бүтжээ. Үүнд “-д, -ж, -л, -р, -рх, -с, -т, -ш, -шаа” зэрэг 9 дагавар бүртгэгдсэн байна. Өөрөөр хэлбэл, дээрх 9 дагаврын аргаар эерэг сэтгэл хөдлөл илэрхийлсэн нийт 88 шинэ үүсмэл үйл үг бүтжээ гэж ойлгож болно. Эдгээрээс хамгийн бүтээлч нь “-л”, “-р” дагавар байв. Энэ нь хэл шинжлэлийн эрдэмтдийн дэвшүүлсэн дүгнэлтдээ нийцэж байна. Хэлний хичээл зааж буй багш нар тухайн хэлний үгийн язгуур, үндэс, дагавар, нөхцөл болон уг үгийн хэрхэн үүссэн зүй тогтлыг сайтар ойлгож, суралцагчдад үгийн гарал болон язгуур, үүр нэгтэй үгийн талаар тайлбарлан таниулахад чухал ач холбогдолтой.Түлхүүр үг: Үгсийн сан, үг бүтэх ёс, шинэ үг, үйл үгийн утга, хэлний хэрэглээ